The Effect of Implementing Quality Standards and Teacher Competencies on the Quality of Student Learning at SMA Negeri 1 Leuwiliang, Bogor Regency - Suryo Lestari; Albertin Pawarrangan; Henny Suharyati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the effect of the implementation of Quality Standards (X1) and Teacher Competence (X2) on the Quality of Learning (Y) at SMA Negeri 1 Leuwiliang, Bogor Regency. Improving the quality of education is a crucial agenda in human resource development, where its success at the school level is largely determined by the synergy between the implementation of systemic standards and the capabilities of individual educators. This study uses a quantitative approach with an explanatory research type to explain the causal relationship between variables. The research sample consisted of 30 teachers selected through a purposive sampling technique. Data collection was carried out using a Likert-scale questionnaire consisting of 50 statements. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results of the analysis show that (1) Quality Standards have a positive and significant effect on the Quality of Learning with a path coefficient of 0.350; (2) Teacher Competence has a positive and significant effect on the Quality of Learning with a path coefficient of 0.550. Simultaneously, the two independent variables explained 68.3% of the variance in the Learning Quality variable. This finding indicates that while structured quality standards are an important foundation, teacher competency is the most influential factor in creating superior learning quality at SMAN 1 Leuwi Liang. The practical implication of this research is the need to prioritize ongoing teacher professional development programs, in addition to ensuring compliance with national education standards.